Road Accident Prediction - Soham Raj Jain (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Road accidents are a global concern, leading to a significant loss of life and property. This paper presents a machine learning-based approach for predicting road accidents by leveraging feature engineering techniques and advanced Ran- dom Forest models. Using enriched datasets with preprocessing methods, the proposed model achieves a predictive accuracy of over 92%. This study also explores key insights from accident data, providing actionable outcomes to improve road safety measures.
Keywords: Road Safety; Machine Learning; Accident Pre- diction; Random Forest; Feature Engineering